THE APPROACH TO THE ANALYSIS OF ELECTRICAL FIELD DISTRIBUTION IN THE SETUP OF PAPER INSULATED ELECTRODES IN OIL - Rozga, Pawel; Hantsz, Dariusz (European Scientific Journal, ESJ, 2013)
﻿Article presents the problem of the approach to the analysis of electrical field distribution in the model insulating system, which, in the author’s experimental research, was used to the assessment of the influence of paper insulation on the mechanism of electrical discharge initiation in mineral oil. The main assumptions of the planned numerical works based on the finite element method were described and scientific aim of the numerical analysis were characterized in this paper. Both the assumptions and the scientific aim were related to the conclusions from the experimental works, especially to the measured times to initiation of the discharges developing in mineral transformer oil, indicating on the important role of the oil quality in the process of discharge initiation in the system of the insulated by paper electrodes immersed in oil.